PENGARUH PENGGUNAAN MEDIA SOSIAL TIK TOK TERHADAP AKHLAK SISWA KELAS IX DI SEKOLAH MENENGAH PERTAMA NEGERI 2 PAMEKASAN TAHUN PELAJARAN 2023-2024 - Abdul Munib; Atnawi Atnawi; Nur Laila (Fakultas Agama Islam Universitas Islam Madura, 2023)
This research is motivated by the use of social media tiktok by students which often raises pros and cons in society. From this background, various kinds of influences will be known, especially on student morals, so that this can have an impact on the morals of the younger generation. The formulation of the problem in this research is; 1). Is there an effect of the use of TikTok social media on the morals of class IX students at Pamekasan 2 Public Junior High School?, 2). How Much Influence Does the Use of TikTok Social Media Have on the Morals of Class IX Students at Public Middle School 2 Pamekasan? The results of this study indicate that; 1). There is a significant influence between variable X on variable Y, this is based on data analysis with a significance level of P-value (0.04) < significance (0.05) then Ha is accepted and Ho is rejected. This means that variable X